Polarization Switching and Hysteresis in Vertical-Cavity Surface-Emitting Lasers Subject to Orthogonal Optical Injection - Salvide, Matias F.; Masoller, Cristina; Torre, Maria Susana (IEEE journal of quantum electronics, 2014)
We study polarization switching and hysteresis in a vertical-cavity surface-emitting laser (VCSEL) subject to an orthogonal optical injection, such that the polarization of the injected light is perpendicular to that of the free-running VCSEL. We use the framework of the spin-flip model to characterize the polarization state of the VCSEL as a function of the frequency detuning. With appropriated injection conditions, the orthogonal polarization turns on and locks to the injected field. Increasing and decreasing the detuning across the two locking boundaries results either in narrow or wide hysteresis cycles, or even in irreversible switching. These results are in a good agreement with recent experimental observations.